Study of Several Types of Lithium-polymer Batteries With 3s Battery Management System. Issue 1 (December 2021) - Karlina, F H; Sunarno,; Waruwu, M M; Wijaya, R
Abstract: Lithium batteries have been identified as one of the most promising energy conversion and storage devices because of their high energy density, safety, and long cycling life. Lithium-polymer batteries have been widely used in various applications ranging from electric vehicles to mobile devices. The purpose of this study was to determine the best type of lithium-polymer and VRLA batteries in the review of the balance of battery life timeout comparison for a predetermined load. Each battery has a different actual balance and theoretical comparison value. The best balance value is close to 1. The best balance comparison after the experiment was a LiPo battery type with a balance value of 0.77 R158F076A7 BMS 3s, then VRLA with a balance of 0.67, and the smallest balance is a LiPo GSE 18650 battery with a balance of 0.25. For both types of batteries with the same input parameters provided, the terminal voltage, current, and characteristics output of Lithium-polymer Li-Po GSE 18650. Batteries were found to be better than a lead-acid with a timeout of use that is 51.64 minutes.